Emergency personnel and magnetic resonance imaging: is there a risk from clothing and working materials?. (2017) - Schmidt, Georg
The use of Magnetic Resonance Imaging (MRI) systems is on the rise and the number of installed systems is constantly increasing. This raises the possibility for emergency personnel to get in contact with these systems. This study examines the effects of magnetic force on selected working materials and clothes of firefighters and paramedics. This study was conducted as a field study, utilising a 1.5 tesla MRI system. The highest force of attraction can be researched on helmets (30 newton), boots (90 newton) and gloves (17 newton). Moreover, working material can be influenced by eddy currents. Considering the results of this study, boots and helmets must be considered as a risk in MRI examination rooms. Additional trainings for firefighters and paramedics should consider the danger of ferromagnetic objects close to MRI systems and that specific material can become a threat. More research is needed to investigate more material of emergency personnel.